THE INFLUENCE OF CUSTOMER VALUE AND BRAND IMAGE ON THE LOYALTY OF NISSAN CAR USERS, AND SATISFACTION AS A MEDIATING VARIABLE - Pradipta Utama, Andyan; Kosasih, Kosasih; Trisnawati, Nana (Dinasti International Journal of Management Science, 2021)
Customer value plays an important role in winning business competition, so we need to find out how much customer value can satisfy customers and make them loyal. Therefore, customer value also needs to be continuously developed through continuous research. In this study, respondents with high customer value will be satisfied with the products they use, and this satisfaction will lead to loyalty to these customers. This is consistent with the research finding that customer value affects loyalty through satisfaction. This research aims to examine the impact of customer value and brand image on loyalty, and to use intermediaries as satisfaction. The research unit is a customer/user of Nissan Motor. The methods used in this study are quantitative, with explanatory methods, more specifically related to causality. According to the research purpose, the data analysis method used is structural equation modelling (SEM), the data is processed using JASP software. Testing is done through direct effects and indirect effects.